ANALISIS PENGARUH EKSPOR, FOREIGN DIRECT INVESTMENT DAN INFLASI TERHADAP CADANGAN DEVISA DI NEGARA ASEAN DALAM PERSPEKTIF EKONOMI ISLAM - Purwanti, Epi; Iqbal, Muhammad; Fasa, Muhammad Iqbal (Bussman Journal : Indonesian Journal of Business and Management, 2024)
Foreign Exchange Reserves are all foreign assets controlled by the monetary authority and can be used at any time for international transactions or payments. This research aims to determine the influence of exports, foreign direct investment and inflation on foreign exchange reserves in seven ASEAN countries in 2013-2022 from an Islamic economic perspective. This research uses descriptive quantitative methods with panel data regression analysis. Panel data is data consisting of time series and cross section data. The analysis tool is eviews 10. The data in this research was obtained from literature studies, namely ASEAN Statistics-Yearbook-2023 and from the World Bank. The research sample was seven ASEAN countries taken from several ASEAN countries. The research results show that the variables export, foreign direct investment and inflation together (simultaneously) have a significant influence on foreign exchange reserves in seven ASEAN countries in 2013-2022. Meanwhile, partially the export variable has a positive and significant effect on foreign exchange reserves in seven ASEAN countries, the foreign direct investment variable has a negative and insignificant effect on foreign exchange reserves in seven ASEAN countries, while the inflation variable has a negative and significant effect on foreign exchange reserves in seven ASEAN countries. Every government action related to the people is always related to their benefit